(untitled) (Medico Legal Update, 2020)
Cigarette smoking is a major risk factor for heart disease and peripheral vascular disorders. The cardiovascular diseases among smokers can be predicted by the levels of lipid profile. The objective of the present study is to analyse the effects of smoking on the lipid profile and lipase levels among Iraqi smokers as well as to identify the morbidity risk among smokers and non-smokers. A cross-sectional study (n=50) was designed including smokers (n=40) and nonsmokers (n=10) as a control group.The lipid profile and lipase level tests were performed after overnight fasting.The lipid profile and lipase levels were found to be significantly (p?0.05) increased in the smoker group as compared to non-smoker group. Total cholesterol and triglyceride (TG) levels were found to be increased 194.24±37.04mg/dl and 173.87±44.96mg/dl in the smoker group as compared to control (165.35±23.6mg/dl and 106.7±43.4mg/dl), respectively. Serum high-density lipoprotein cholesterol (HDL) concentration was decreased to 46.30±7.1mg/dl as compared to control group 64.15±8.8mg/dl.The smoker group showed significant increased in the serum LDL (103.16±21.43mg/dl) and VLDL (44.78±8.9mg/dl) levels as compared to control group (77.06±20.5md/dl and 24.14±8.8mg/dl, respectively). Similarly, the smoker group showed decreased in serum lipase level (28.35±78.3) as compared to the control group (37.65±9.7). Smoking is associated with many risk factors of heart and vascular diseases which can evaluated by the elevated levels of total cholesterol, TG, LDL and VLDL. However, preventive strategies are needed to avoid the future cardiovascular diseases and in supporting the benefits of quitting smoking.